2023
DOI: 10.1002/hsr2.1231
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to type 2 diabetes management among slum‐dwellers: A systematic review and qualitative meta‐synthesis

Abstract: Background and Aims The prevalence of type 2 diabetes (T2D) is on the rise worldwide, especially in developing countries. There is a significant difference between the slum‐dwellers and other urban dwellers in terms of T2D incidence rate and access to healthcare services. This review aimed to identify barriers and facilitators to T2D management among slum‐dwellers. Methods A systematic review was conducted to identify barriers and facilitators to T2D management from January 1, 2002 to May 30, 2022. We searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
(467 reference statements)
0
9
0
Order By: Relevance
“…This review revealed that individual, health system, and contextual factors influence type 2 diabetes management among slum dwellers. The review recommended that policymakers use the findings to reduce barriers and augment facilitators of type 2 diabetes management among slum dwellers [ 29 ]. A study conducted in 2023 explored barriers to healthcare utilization among patients with type 2 diabetes living in slums from the providers' perspective.…”
Section: Discussionmentioning
confidence: 99%
“…This review revealed that individual, health system, and contextual factors influence type 2 diabetes management among slum dwellers. The review recommended that policymakers use the findings to reduce barriers and augment facilitators of type 2 diabetes management among slum dwellers [ 29 ]. A study conducted in 2023 explored barriers to healthcare utilization among patients with type 2 diabetes living in slums from the providers' perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent findings of unfavourable facility environments have been elucidated by other relevant studies [ 15 , 21 , 37 , 38 ]. A systematic and qualitative meta-synthesis study revealed significant service delivery network problems, particularly among low-middle-income countries where most of the diabetes health services are provided by public clinics established within hospitals in district and regional capitals [ 39 ]. The shortage of diabetes care specialists revealed in this study is similar to what was found in a multicenter cross-sectional study conducted in Northwest Ethiopia among diabetes patients where participants reported a shortage of trained endocrinologists and high patient load to be a setback towards their treatment satisfaction [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes in deprived and informal settlement communities has been linked to physical inactivity, unhealthy diet, being overweight and obese, and cigarette smoking [ 10 ]; and shaped by individual factors, contextual factors, and health system-related factors [ 49 ]. We found a relatively high prevalence of the different NCD risk factors, but a lower prevalence of diabetes compared to other countries in West Africa [ 29 ].…”
Section: Discussionmentioning
confidence: 99%